Stress and coping strategy among coaching and non-coaching students in Kota: A comparative study - B S Shekhawat; Deepika Meena; Sandhya Yadav; Vikas Dhaka; K Vignesh (Industrial Psychiatry Journal, 2023)
Background: About 1.5 lakh students study in over 100 coaching centers in Kota. There is a highly competitive environment, and students often land up in stress and even suicide. So, the estimation of the magnitude of this problem and timely intervention can be of great value to students. Aim: This study aimed to assess and compare stress and coping strategies used by coaching and non-coaching students studying in Kota. Material and Methods: This cross-sectional study included 90 coaching and 90 non-coaching students fulfilling inclusion criteria that were specifically laid down for the study. A semi-structured specially designed pro forma, Scale of Academic Stress (SAS), and Coping Strategies Scale (CSS)-Hindi version were used. Appropriate statistical methods were then used to classify, tabulate, and analyze the collected data. Results: In this study, it was found that of all coaching students, 44.45% were suffering from high levels of academic stress, 34.44% suffered from average and 21.11% reported suffering from low levels of academic stress. Likewise, among non-coaching students, 70% were suffering from low academic stress, 26.67% from average, and 3.33% from high levels of academic stress. It was also evident that the majority of both coaching and non-coaching students used a low level of active coping strategy (cognitive approach, behavioral approach, and cognitive behavioral approach) and a high level of avoidance coping strategy (cognitive avoidance and behavioral avoidance). Conclusion: There is a significantly high prevalence of stress among coaching students as compared to non-coaching students. Stress levels of greater severity were found to be more prevalent in female students, 12th-class students, those belonging to urban and middle-class backgrounds, and those whose stream was chosen by their parents. Both coaching and non-coaching students used the same type of coping strategies to cope with stress.